Ameloblastic carcinoma arising from a preexistent ameloblastoma - Hugo Costa Neto; Andrea F. Carmo; Ana Luiza D. L. Andrade; Rodrigo R. Rodrigues; Adriano R. Germano; Roseana A. Freitas; Hébel C. Galvão (Sociedade Brasileira de Patologia Clínica, 2019)
ABSTRACT Ameloblastic carcinoma (AC) is a rare odontogenic tumor that represents the malignant counterpart of an ameloblastoma. There are few cases of AC in the English-language literature, with only 16 cases arising from preexisting ameloblastomas reported in the last 10 years. Multiple local recurrences of ameloblastomas precede this transformation. In the current report, we describe a case of AC at the posterior maxilla in a 42-year-old female submitted to surgical resection, with three recurrences of ameloblastoma in a period of four years. Imaging exams showed a radiodense mass with cortical bone disruption and maxillary sinus invasion. Histologic analysis demonstrated features of islands and nests of malignant epithelium transformation, atypia, pleomorphic cells, nuclear hyperchromatism, necrosis and desmoplasia. AC represents a rare and challenging histologic diagnosis. Surgical access with adequate hard and soft tissue margins is essential for influencing survival. The description of new cases may reveal, through of treatment and clinical follow-up, characteristics that allow us better understanding of AC behavior.